Creativity and humor as mental fitness indicators mate selection among college students in Iloilo City. - Escorpiso, Ariane Mhae E.
It has been argued that certain traits evolved, at least in part, through sexual selection to attract mates. This study was done to examine mental traits, specifically, creativity and sense of humor in relation to mate selection. Unlike other previous researches, creativity was further explored by incorporating various domains (self/everyday, scholarly, performance, scientific/mechanical, and artistic) using a self-report questionnaire. On the other hand, sense of humor was measured through the Multidimensional Sense of Humor Scale. A general tendency to engage in creative behaviors was related to the score on the behavioral facet of the revised Sociosexual Orientation Inventory. Participants high in creativity were chosen more often as mate but this relationship was only true for males. However, findings of this study revealed that the relationship between sense of humor and mate selection was insignificant.